Comparative evaluation of the effect of plant extract, Thymus vulgaris and commercially available denture cleanser on the flexural strength and surface roughness of denture base resin - Bose Babu Namala; Veena Hegde (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aims to evaluate and compare the effect of plant extract (thyme essential oil solution) and commercially available denture cleanser on the flexural strength and surface roughness of denture base resin. Settings and Design: Comparative In-vitro study. Chemical denture cleansers play a vital role in maintaining the hygiene and serviceability of the dentures. Bacterial resistance to these chemical agents paved way to plant-extracts as novel denture cleansing agents. However, the effect of these plant-extract denture cleansers on the physical and surface characteristics of denture base resins has not been evaluated. Material and Methods: A total of 90 heat polymerizing denture base material (Trevalon, Dentsply) samples were fabricated and divided into 3 groups with 30 samples each. Samples from each group were immersed in their respective denture cleanser solution (Group A- Distilled water(control); Group B- Fittydent denture cleanser; Group C- Thyme essential oil solution denture cleanser) for a simulated overnight 8hr immersion for 180 days. The samples were evaluated for increase in surface roughness and flexural strength using Tally-surf Surface Profiler and Instron Universal Testing Machine respectively. Results obtained were statistically analyzed using one-way ANOVA. Statistical Analysis Used: Oneway ANOVA , Post hoc Tukey's test. Results: Thyme essential oil solution group showed minimal increase in surface roughness (ΔRa) with values comparable to that of the control group which had the least increase in surface roughness and Fittydent group showed significant increase (P < 0.05) in surface roughness. For flexural strength, statistically significant difference (P < 0.05) was observed among the three groups with Fittydent group showing the highest flexural strength followed by control group and Thyme essential oil solution group. However, the decrease in the flexural strength was not of clinical significance. Conclusion: Plant extract - thyme essential oil denture cleanser was superior in preserving the surface roughness of denture base resins compared to commercially available denture cleanser. Clinically significant difference in flexural strength was not observed between the denture cleanser groups.